2010
DOI: 10.1534/genetics.110.120519
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Extracellular Matrix Remodeling During Organ Growth Using the Caenorhabditis elegans Pharynx Model

Abstract: The organs of animal embryos are typically covered with an extracellular matrix (ECM) that must be carefully remodeled as these organs enlarge during post-embryonic growth; otherwise, their shape and functions may be compromised. We previously described the twisting of the Caenorhabditis elegans pharynx (here called the Twp phenotype) as a quantitative mutant phenotype that worsens as that organ enlarges during growth. Mutations previously known to cause pharyngeal twist affect membrane proteins with large ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 68 publications
(60 reference statements)
1
16
0
Order By: Relevance
“…Within the region of PAS136 mapping, there are 322 genes; 39 were chosen for screening using recorded L1 arrest as a necessary parameter; experiments showing pharynx phenotypes are listed (Table 4). A partially penetrant phenotype similar to that of PAS136 resulted from lam-3 (T22A3.8) RNAi and blmp-1 (F25D7.3) RNAi (Figure 3C and D); the laminin gene lam-3 has previously been shown to affect the extracellular matrix and pharynx cohesion, while blmp-1 is described as a homolog of the B lymphocyte-induced maturation protein 1 on WormBase [24], [25]. Other pharyngeal phenotypes were observed that did not mimic PAS136, such as the Pun phenotypes of mom-5 (T23F8.1) and hmr-1 (W02B9.1) (data not shown and Figure 3E).…”
Section: Resultsmentioning
confidence: 93%
“…Within the region of PAS136 mapping, there are 322 genes; 39 were chosen for screening using recorded L1 arrest as a necessary parameter; experiments showing pharynx phenotypes are listed (Table 4). A partially penetrant phenotype similar to that of PAS136 resulted from lam-3 (T22A3.8) RNAi and blmp-1 (F25D7.3) RNAi (Figure 3C and D); the laminin gene lam-3 has previously been shown to affect the extracellular matrix and pharynx cohesion, while blmp-1 is described as a homolog of the B lymphocyte-induced maturation protein 1 on WormBase [24], [25]. Other pharyngeal phenotypes were observed that did not mimic PAS136, such as the Pun phenotypes of mom-5 (T23F8.1) and hmr-1 (W02B9.1) (data not shown and Figure 3E).…”
Section: Resultsmentioning
confidence: 93%
“…In addition to non-neuronal functions (Grana et al, 2010; Jafari et al, 2010; Lynch et al, 2012), sax-7 /L1CAM is important for development and maintenance of different aspects of the nervous system (Sasakura et al, 2005; Wang et al, 2005; Pocock et al, 2008; Dong et al, 2013; Salzberg et al, 2013; Opperman et al, 2015). Interestingly, distinct domains of the protein are necessary for different processes.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what drives this effect on sheath cell integrity, but it has been speculated that it is mediated by a loss of adhesion signals to the cells from the Unc-52-depleted basement membrane. Unc-52 mutation or depletion has been tied to developmental defects in the pharynx (Jafari et al, 2010; Morck et al, 2010). …”
Section: Evolutionary Origins Reveal Association With Establishmenmentioning
confidence: 99%